Two new species of freshwater Macrostomum (Rhabditophora: Macrostomorpha) found in China - Lin, Yitao; Zhou, Weiwei; Xiao, Peng; Zheng, Yihong; Lu, Jun; Li, Jiancheng; Wang, Antai (Zootaxa, 2017)
There is limited information about the ecology of freshwater flatworms in China, in particular, the members of the genus Macrostomum. Surveying freshwater bodies to explore the species diversity is the first step to obtain more ecological information about those flatworms. We hereby report the discovery of two new species of freshwater flatworms in Macrostomum. Macrostomum chongqingensis Lin and Wang, n. sp. was discovered from stones in the shallow water of Jialing River bed near Chongqing. Macrostomum zhaoqingensis Lin and Wang, n. sp. was discovered in the water of Xing Lake near Zhaoqing city, Guangdong province. Xing Lake is a part of an ancient river that has changed its course. For each species, we describe the morphology of the whole specimen, penis stylet, and sperm, as well as other internal anatomical features based on serial sections. We determined 18S, 28S rDNA and COI sequences from the two new species, and performed a phylogenetic analysis to confirm the status and evolutionary position of the two new species. We discuss the significance of our discoveries in terms of flatworm biodiversity studies in China and the Oriental realm.